Organizational Transformation in Adopting Hybrid Work Models: A Literature Review on Organizational Changes and Employee Readiness - Hasyim, Hasyim; Bakri, Muhammad (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study explores the implications of hybrid work models on organizational dynamics and employee well-being. Through a qualitative literature review approach, the research examines existing literature on hybrid work, focusing on organizational changes, employee readiness, and long-term effects. The methodology systematically reviews scholarly articles, books, and academic sources, synthesizing key themes, theoretical frameworks, and empirical findings. The results reveal mixed findings regarding the impact of hybrid work on various aspects of organizational functioning and employee experiences. While hybrid work offers opportunities for flexibility and autonomy, it also presents challenges such as communication barriers, blurred boundaries between work and personal life, and uncertainties regarding career advancement. Longitudinal studies and comparative analyses across industries, cultures, and geographic regions are recommended to track the evolution of hybrid work arrangements and assess their sustainability in dynamic environments. Interdisciplinary approaches and integrating emerging technologies can contribute to evidence-based decision-making and foster innovation in hybrid work design and implementation.